Carbon fibre reinforced cement-based composites as smart floor heating materials. (1st April 2016) - Hambach, Manuel; Möller, Hendrik; Neumann, Thomas; Volkmer, Dirk
Abstract: A systematic development of an electrically heatable cement-based composite, prepared by admixing a few volume percent of chopped carbon fibres without a need of adding further heating elements, is reported. The optimal volume content of carbon fibres is determined to range from 1 to 2 volume percent, if 3 mm long and 7 μm thick carbon fibres are being used. By applying an electrical current to the composite material, a temperature rise suitable for heating rooms and walls can be induced. Mechanical tests show that the flexural strength of carbon fibre reinforced composite is not decreasing during electrical heating at 60 °C for 4 weeks. For electrical heating purposes, graphite or silver is found to be the best electrode material.